Creative workshop as a method of artistic education at non-artistic faculties. - Marcin Emil Cabak (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
This article discusses the role of a didactic method called creative Workshop in the artistic education of students at non-artistic faculties. The first part of the article is an analysis of the term creative Workshop. The origins, history and the place of the creative Workshp method in the art domain is discussed. specifics of using this method at non-artistics faculties are also presented. The second part describes workshops which took place at an university with an non-artistic profile. The third part contains conclusions. The fourth part presents examples of works created during workshops.